MoreMilk Project: Safer milk, better business - International Livestock Research Institute (International Livestock Research Institute, 2020)
The MoreMilk project works with milk vendors and their customers in the informal sector in and around Kasarani sub-county in Nairobi, Kenya. The project started in October 2019 and will conclude in December 2020. MoreMilk will train owners and workers in informal businesses that sell unpacked milk, monitor the safety of the milk they produce and the overall performance of their businesses and assess the empowerment of vendors, especially women. The project will also focus on households that buy unpacked milk and have children under four years. It will monitor if the milk intake of children and the status of their nutrition changes overtime as a result of training given to milk vendors. The study for the MoreMilk project is conducted by the International Livestock Research Institute (ILRI) and partners.